NARA-WPE: A Python package for weighted prediction error dereverberation in Numpy and Tensorflow for online and offline processing - Drude, Lukas; Heymann, Jahn; Boeddeker, Christoph; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
NARA-WPE is a Python software package providing implementations of the weighted prediction error (WPE) dereverberation algorithm. WPE has been shown to be a highly effective tool for speech dereverberation, thus improving the perceptual quality of the signal and improving the recognition performance of downstream automatic speech recognition (ASR). It is suitable both for single-channel and multi-channel applications. The package consist of (1) a Numpy implementation which can easily be integrated into a custom Python toolchain, and (2) a TensorFlow implementation which allows integration into larger computational graphs and enables backpropagation through WPE to train more advanced front-ends. This package comprises of an iterative offline (batch) version, a block-online version, and a frame-online version which can be used in moderately low latency applications, e.g. digital speech assistants.

Machine learning techniques for semantic analysis of dysarthric speech: An experimental study - Despotovic, Vladimir; Walter, Oliver; Haeb-Umbach, Reinhold (Speech Communication 99 (2018) 242-251 (Elsevier B.V.))
We present an experimental comparison of seven state-of-the-art machine learning algorithms for the task of semantic analysis of spoken input, with a special emphasis on applications for dysarthric speech. Dysarthria is a motor speech disorder, which is characterized by poor articulation of phonemes. In order to cater for these noncanonical phoneme realizations, we employed an unsupervised learning approach to estimate the acoustic models for speech recognition, which does not require a literal transcription of the training data. Even for the subsequent task of semantic analysis, only weak supervision is employed, whereby the training utterance is accompanied by a semantic label only, rather than a literal transcription. Results on two databases, one of them containing dysarthric speech, are presented showing that Markov logic networks and conditional random fields substantially outperform other machine learning approaches. Markov logic networks have proved to be especially robust to recognition errors, which are caused by imprecise articulation in dysarthric speech.

Deep Attractor Networks for Speaker Re-Identifikation and Blind Source Separation - Drude, Lukas; von Neumann, Thilo; Haeb-Umbach, Reinhold (ICASSP 2018, Calgary, Canada)
Deep clustering (DC) and deep attractor networks (DANs) are a data-driven way to monaural blind source separation. Both approaches provide astonishing single channel performance but have not yet been generalized to block-online processing. When separating speech in a continuous stream with a block-online algorithm, it needs to be determined in each block which of the output streams belongs to whom. In this contribution we solve this block permutation problem by introducing an additional speaker identification embedding to the DAN model structure. We motivate this model decision by analyzing the embedding topology of DC and DANs and show, that DC and DANs themselves are not sufficient for speaker identification. This model structure (a) improves the signal to distortion ratio (SDR) over a DAN baseline and (b) provides up to 61% and up to 34% relative reduction in permutation error rate and re-identification error rate compared to an i-vector baseline, respectively.

Dual Frequency- and Block-Permutation Alignment for Deep Learning Based Block-Online Blind Source Separation - Drude, Lukas; Higuchi,, Takuya; Kinoshita, Keisuke; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2018, Calgary, Canada)
Deep attractor networks (DANs) are a recently introduced method to blindly separate sources from spectral features of a monaural recording using bidirectional long short-term memory networks (BLSTMs). Due to the nature of BLSTMs, this is inherently not online-ready and resorting to operating on blocks yields a block permutation problem in that the index of each speaker may change between blocks. We here propose the joint modeling of spatial and spectral features to solve the block permutation problem and generalize DANs to multi-channel meeting recordings: The DAN acts as a spectral feature extractor for a subsequent model-based clustering approach. We first analyze different joint models in batch-processing scenarios and finally propose a block-online blind source separation algorithm. The efficacy of the proposed models is demonstrated on reverberant mixtures corrupted by real recordings of multi-channel background noise. We demonstrate that both the proposed batch-processing and the proposed block-online system outperform (a) a spatial-only model with a state-of-the-art frequency permutation solver and (b) a spectral-only model with an oracle block permutation solver in terms of signal to distortion ratio (SDR) gains.

Exploring Practical Aspects of Neural Mask-Based Beamforming for Far-Field Speech Recognition - Boeddeker, Christoph; Erdogan, Hakan; Yoshioka, Takuya; Haeb-Umbach, Reinhold (ICASSP 2018, Calgary, Canada)
This work examines acoustic beamformers employing neural networks (NNs) for mask prediction as front-end for automatic speech recognition (ASR) systems for practical scenarios like voice-enabled home devices. To test the versatility of the mask predicting network, the system is evaluated with different recording hardware, different microphone array designs, and different acoustic models of the downstream ASR system. Significant gains in recognition accuracy are obtained in all configurations despite the fact that the NN had been trained on mismatched data. Unlike previous work, the NN is trained on a feature level objective, which gives some performance advantage over a mask related criterion. Furthermore, different approaches for realizing online, or adaptive, NN-based beamforming are explored, where the online algorithms still show significant gains compared to the baseline performance.

Efail: Breaking S/MIME and OpenPGP Email Encryption using Exfiltration Channels - Poddebniak, Damian; Dresen, Christian; Müller, Jens; Ising, Fabian; Schinzel, Sebastian; Friedberger, Simon; Somorovsky, Juraj; Schwenk, Jörg (27th USENIX Security Symposium (USENIX Security 18))

Return Of Bleichenbacher\textquoterights Oracle Threat (ROBOT) - Böck, Hanno; Somorovsky, Juraj; Young, Craig (27th USENIX Security Symposium (USENIX Security 18))

Security Analysis of eIDAS -- The Cross-Country Authentication Scheme in Europe - Engelbertz, Nils; Erinola, Nurullah; Herring, David; Somorovsky, Juraj; Mladenov, Vladislav; Schwenk, Jörg (12th USENIX Workshop on Offensive Technologies (WOOT 18))

Modelling the Interface of Hybrid Metal-FRP Components Joint by Form Closures - Triebus, Marcel; Tröster, Thomas; Camberg, Alan Adam; Bienia, S.; Dröder, K. (15. Deutsches LS-Dyna Forum)

The influence of damage accumulation on failure prediction: a comparative assessment of *MAT_224 and *MAT_024 + GISSMO for the application in non-isothermal sheet metal forming - Camberg, Alan Adam; Tröster, Thomas; Schneidt , A.; Sotirov , N.; Tölle, J. (15. Deutsches LS-Dyna Forum)

Controlling nonlinear PDEs using low-dimensional bilinear approximations obtained from data - Peitz, Sebastian (arXiv:1801.06419)
In a recent article, we presented a framework to control nonlinear partial differential equations (PDEs) by means of Koopman operator based reduced models and concepts from switched systems. The main idea was to transform a control system into a set of autonomous systems for which the optimal switching sequence has to be computed. These individual systems can be approximated very efficiently by reduced order models obtained from data, and one can guarantee equality of the full and the reduced objective function under certain assumptions. In this article, we extend these results to continuous control inputs using convex combinations of multiple Koopman operators corresponding to constant controls, which results in a bilinear control system. Although equality of the objectives can be carried over when the PDE depends linearly on the control, we show that this approach is also valid in other scenarios using several flow control examples of varying complexity.

Analyzing high-dimensional time-series data using kernel transfer operator eigenfunctions - Klus, Stefan; Peitz, Sebastian; Schuster, Ingmar (arXiv:1805.10118)
Kernel transfer operators, which can be regarded as approximations of transfer operators such as the Perron-Frobenius or Koopman operator in reproducing kernel Hilbert spaces, are defined in terms of covariance and cross-covariance operators and have been shown to be closely related to the conditional mean embedding framework developed by the machine learning community. The goal of this paper is to show how the dominant eigenfunctions of these operators in combination with gradient-based optimization techniques can be used to detect long-lived coherent patterns in high-dimensional time-series data. The results will be illustrated using video data and a fluid flow example.

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Erratum: Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory [Phys. Rev. Materials 1, 034401 (2017)] - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)

Fachsensibilität als Ressource für den Writing Fellow-Ansatz - Frahnert, Vanessa; Karsten, Andrea (Lehren und Lernen mit Writing Fellows. Beiträge zur Forschung, Evaluation und Adaption)
Vanessa Frahnert und Andrea Karsten stellen ihr Textograph*innen-Programm zur Unterstützung des Schreibens in der Lehre vor, das seit dem Sommersemester 2016 zum regelmäßigen Angebot des Kompetenzzentrums Schreiben der Universität Paderborn gehört. Das Programm baut auf den grundlegenden Prinzipien und Überlegungen des Writing Fellow-Konzepts auf, ist aber an die theoretische Ausrichtung des Schreibzentrums sowie die Gegebenheiten der Universität angepasst. Der Beitrag stellt das Programm und seine theoretischen Hintergründe vor und arbeitet die Unterschiede im Vergleich zum Writing Fellow-Ansatz heraus.

Selbstoptimierung - Tönsing, Johanna (Von Automatismen bis Zersetzung. Wörterbuchprojekt des Graduiertenkollegs Automatismen)

Matthäus Merians Paderborn-Darstellung in der ›Topographia Westphaliæ‹. [Laudatio auf Markus Lauert] - Süßmann, Johannes (Neujahrsempfang der Universität Paderborn 21. Januar 2018. Laudationes)

Open Science-Forschung und qualitative Methoden – fünf Ebenen der Reflexion - Steinhardt, Isabel (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Ausgehend von den fünf Schulen von Open Science von Fecher und Friesicke (2014) findet in diesem Beitrag eine Reflexion eines qualitativen Open Science-Forschungsprojektes statt. Mit der Reflexion wird der Offenlegung und Transparenz, die Open Science-Projekten immanent ist, entsprochen. Es soll aber auch zukünftigen Forscherinnen und Forschern, die überlegen ein Open Science Projekt zu starten, dabei helfen mögliche Hürden aber auch Lösungswege zu antizipieren. Als Reflexionsbeispiel dient das Projekt «Nutzung digitaler Medien und Habitus von Studierenden», das auf folgenden fünf Ebenen betrachtet wird: Ebene der Wissensproduktion; Ebene der freien Zugänglichkeit von Wissen; Ebene der Infrastruktur; Ebene der kollaborativen Forschung und Ebene der Impakt-Messung.
Keywords: Mediendidaktik; Hochschule; Open Science

Accelerating Molecular Dynamic Simulations by Offloading Fast Fourier Transformations to FPGA - Ramaswami, Arjun
Molecular Dynamic (MD) simulations are computationally intensive and accelerating them using specialized hardware is a topic of investigation in many studies. One of the routines in the critical path of MD simulations is the three-dimensional Fast Fourier Transformation (FFT3d). The potential in accelerating FFT3d using hardware is usually bound by bandwidth and memory. Therefore, designing a high throughput solution for an FPGA that overcomes this problem is challenging. In this thesis, the feasibility of offloading FFT3d computations to FPGA implemented using OpenCL is investigated. In order to mask the latency in memory access, an FFT3d that overlaps computation with communication is designed. The implementa- tion of this design is synthesized for the Arria 10 GX 1150 FPGA and evaluated with the FFTW benchmark. Analysis shows a better performance using FPGA over CPU for larger FFT sizes, with the 643 FFT showing a 70% improvement in runtime using FPGAs. This FFT3d design is integrated with CP2K to explore the potential in accelerating molecular dynamic simulations. Evaluation of CP2K simulations using FPGA shows a 41% improvement in runtime in FFT3d computations over CPU for larger FFT3d designs.
Keywords: FFT: FPGA; CP2K; OpenCL

Schnittstellenaufgaben im Praxiseinsatz: Aufgabenbeispiel zur „Bleistiftstetigkeit“ und allgemeine Überlegungen zu möglichen Problemen beim Einsatz solcher Aufgaben - Hoffmann, Max (Beiträge zum Mathematikunterricht 2018)

Professionalisierung von Grundschullehrkräften – wissenschaftlich fundiert, praxisorientiert und reflexionsbasiert - Frey, Anne; Buhl, Heike M. (Zeitschrift für Grundschulforschung)
Die Professionalisierung von Grundschullehrkräften mit den speziellen an sie gestellten Anforderungen sowie den Erwartungen der Studierenden bewegt sich zwischen der Notwendigkeit einer wissenschaftlich-konzeptuellen Basis und der Ausrichtung auf die schulische Praxis. Verbindendes Element ist eine gut angeleitete Reflexion. Dieser Dreiklang wird professionstheoretisch begründet, wobei unterschiedliche Ansätze jeweils eigene Impulse für die Lehrerbildung leisten. Vor diesem Hintergrund werden Curricula und hochschuldidaktische Maßnahmen diskutiert. Exemplarisch werden Projekte beschrieben, die in unterschiedlichen Formaten zur Reflexion von Praxis auf theoretischer Basis anregen.
Keywords: Grundschule; Lehrerbildung; Reflexion; Theorie-PraxisVerzahnung; Hochschuldidaktik; Professionstheorie

Intergenerational Transfers: Associations with Adult Children’s Emotional Support of Their Parents - Sommer, Sabrina; Buhl, Heike M. (Journal of Adult Development)
This study investigates how different factors in regard to intergenerational relationships are associated with emotional support given by adults to their parents. The analysis focuses on adult children and their parents in a representative German sample. Data were obtained from the second wave of the German Family Panel (pairfam) consisting of 2064 women and 1841 men. Results show that transfer of emotional support by the adult children was especially associated not only with received emotional support from parents, but also with affection, conflicts, and expectations concerning parents. A moderator analysis focuses on gender and showed differences for the association between given support by adults and conflicts between mothers and fathers. For the offspring, no gender effects were found.
Keywords: Intergenerational relationships; Emotional support; Solidarity; Adult children; Gender

Fallbasierte Modulabschlussprüfungen zur Verzahnung von Theorie und Praxis im Master des Lehramtsstudiums - Buhl, Heike M.; Bohndick, Carla; Bonanati, Sabrina; Greiner, Christian; Hilkenmeier, Johanna; Kordts-Freudinger, Robert (Psychologiedidaktik und Evaluation XII)

Externe und interne Qualitätssicherung von Studium und Lehre durch Akkreditierungs- und Evaluationsverfahren - Steinhardt, Isabel; Schneijderberg, Christian; Krücken, Georg; Baumann, Janosch
Mit diesem Working Paper werden die wesentlichen Ergebnisse des INCHER-Forschungsprojekts „Externe und interne Qualitätssicherung von Studium und Lehre durch Akkreditierungs- und Evaluationsverfahren“ (kurz EIQSL) zusammengefasst. Dabei ging es um die Rekonstruktion und Einordnung der externen Qualitätssicherung im Rahmen der allgemeinen hochschulpolitischen Governance, das vielschichtige Qualitätsverständnis, das den Verfahren der Qualitätssicherung unterliegt, die hochschulinternen Prozesse und Strukturen der Qualitätssicherung, die Besonderheiten des Peer Reviews in Akkreditierungsverfahren sowie das komplexe Verhältnis zentraler Akteure zueinander. Zusammenfassend zeigte sich – über die Detailergebnisse hinaus –, dass die externe Qualitätssicherung an Hochschulen durch Akkreditierung nach wie vor umstritten ist. Die theoretisch auf der Grundlage des Neo-Institutionalismus und der Systemtheorie begründete Erwartung der Autoren, dass sich Institutionalisierungsprozesse aufzeigen lassen, die zu einer schrittweisen, im Zeitverlauf beobachtbaren „Normalisierung“ führen, wurde nicht erfüllt. Zusätzlich ist nicht nur die Legitimation des Systems kontrovers und umstritten, sondern auch die seiner Effekte. Es zeigten sich unterschiedliche, teils positiv, teils negativ bewertete Effekte, die sich - will man nicht unzulässig verallgemeinern - nicht zu einer wissenschaftlichen Gesamteinschätzung aggregieren lassen.

Semantic Data Mediator: Linking Services to Websites - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing -- ICSOC 2017 Workshops)
Many websites offer links to social media sites for convenient content sharing. Unfortunately, those sharing capabilities are quite restricted and it is seldom possible to share content with other services, like those provided by a user's favorite applications or smart devices. In this paper, we present Semantic Data Mediator (SDM) --- a flexible middleware linking a vast number of services to millions of websites. Based on reusable repositories of service descriptions defined by the crowd, users can easily fill a personal registry with their favorite services, which can then be linked to websites by SDM. For this, SDM leverages semantic data, which is already available on millions of websites due to search engine optimization. Further support for our approach from website or service developers is not required. To enable the use of a broad range of services, data conversion services are automatically composed by SDM to transform data according to the needs of the different services. In addition to linking web services, various service adapters allow services of applications and smart devices to be linked as well. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.

Supporting the Cognitive Process in Annotation Tasks - Seemann, Nina; Geierhos, Michaela; Merten, Marie-Luis; Tophinke, Doris; Wever, Marcel Dominik; Hüllermeier, Eyke (Postersession Computerlinguistik der 40. Jahrestagung der Deutschen Gesellschaft für Sprachwissenschaft)

Enhanced Security of Attribute-Based Signatures - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (The International Conference on Cryptology And Network Security (CANS))

Delegatable Attribute-based Anonymous Credentials from Dynamically Malleable Signatures - Blömer, Johannes; Bobolz, Jan (ACNS 2018 Applied Cryptography & Network security)
In this paper, we introduce the notion of delegatable attribute-based anonymous credentials (DAAC). Such systems offer fine-grained anonymous access control and they give the credential holder the ability to issue more restricted credentials to other users. In our model, credentials are parameterized with attributes that (1) express what the credential holder himself has been certified and (2) define which attributes he may issue to others. Furthermore, we present a practical construction of DAAC. For this construction, we deviate from the usual approach of embedding a certificate chain in the credential. Instead, we introduce a novel approach for which we identify a new primitive we call dynamically malleable signatures (DMS) as the main ingredient. This primitive may be of independent interest. We also give a first instantiation of DMS with efficient protocols.

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Die Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) – Zentrale Befunde - Wild, Elke; Lütje-Klose, Birgit; Neumann, Phillip; Gorges, Julia (DDS – Die Deutsche Schule)
In der Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) wurden die psychosoziale und die Leistungsentwicklung bei Kindern mit sonderpädagogischem Förderbedarf im Förderschwerpunkt „Lernen“ von der 3. bis zur 5. Klasse in unterschiedlichen Fördersettings untersucht. Die Ergebnisse quantitativer und qualitativer Zugänge zeigen, dass vor allem proximale Faktoren auf der Ebene der Einzelschule – weniger die Form der Beschulung – für die Entwicklung der Kinder relevant sind.
Keywords: BiLieF; Inklusion; sonderpädagogischer Förderbedarf; Grundschule; Wohlbefinden; Rollenausprägungen sonderpädagogischer Lehrkräfte

ESPnet: End-to-End Speech Processing Toolkit - Watanabe, Shinji; Hori, Takaaki; Karita, Shigeki; Hayashi, Tomoki; Nishitoba, Jiro; Unno, Yuya; Enrique Yalta Soplin, Nelson; Heymann, Jahn; Wiesner, Matthew; Chen, Nanxin; Renduchintala, Adithya; Ochiai, Tsubasa (INTERSPEECH 2018, Hyderabad, India)
This paper introduces a new open source platform for end-toend speech processing named ESPnet. ESPnet mainly focuses on end-to-end automatic speech recognition (ASR), and adopts widely-used dynamic neural network toolkits, Chainer and Py-Torch, as a main deep learning engine. ESPnet also follows the Kaldi ASR toolkit style for data processing, feature extraction/format, and recipes to provide a complete setup for speech recognition and other speech processing experiments. This paper explains a major architecture of this software platform, several important functionalities, which differentiate ESPnet from other open source ASR toolkits, and experimental results with major ASR benchmarks.

Big Data-Kriege. Über Tötungslisten, Drohnen und die Politik der Datenbanken - Weber, Jutta (Machine Learning – Medien, Infrastrukturen und Technologien der Künstlichen Intelligenz)

Tagungsbericht: Kulturen der Moral – Moral Cultures. Internationale und interdisziplinäre Tagung in Kooperation mit der DGEJ vom 19. bis 22. September 2018 an der Universität Paderborn. - Becker, Rieke; Heidgen, Michael; Lauert, Markus; Witschel, Verena

Accreditation of X Qualities Instead of Quality X: A Normative Analysis of Criteria of the German Higher Education Accreditation Regime - Schneijderberg, Christian; Steinhardt, Isabel (Higher Education Policy)
This article examines the normative roots of criteria used for the accreditation of study programs in German higher education based on the orders of worth framework by Boltanski and Thévenot (On justification. Economies of worth, Princeton University Press, Princeton, 2006). From 1999 to 2017, the criteria have been subject to continuous efforts of legitimation, especially by the German Länder, which are in charge of public higher education in Germany. The empirical analysis shows that industrial (e.g., ‘standardization’), civic (e.g., ‘gender justice and equal opportunities’), and civic-industrial (e.g., ‘employability’) codings are the core of accreditation criteria. The normativity of these criteria constitutes accreditation as a technical arrangement running (a) a structural program (e.g., qualifications of academic teachers, modularization of study programs, and quality management) and (b) a political program (e.g., diversity of students and system of studies). Based on the empirical analysis, it is concluded that X does not stand for the accreditation of quality X. X stands for the accreditation of X qualities for specific normative purposes via the higher education accreditation regime.

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

Körper, Materialitäten, Technologien

Degendering the Driver? Special Issue of ‚Transfers. International Journal for Mobility Studies‘, Vol. 8(1) (Transfers. International Journal for Mobility Studies)

Wer handelt mit unsichtbaren Schnittstellen? - Alpsancar, Suzana (Unterwachen und Schlafen. Anthropophile Medien nach dem Interface)

Quantitative Explanation as a Tight Coupling of Data, Model, and Theory - Krüger, Alexander; Tünnermann, Jan; Rohlfing, Katharina; Scharlau, Ingrid (Archives of Data Science, Series A)
What does it mean to explain data patterns? Cognitive psychologists and other scientists face this question when observable phenomena have to be explained in theoretical terms. Frequentist null-hypothesis testing – one prominent approach in psychology – controls error rates. Machine learning – an alternative prominent outside of, but not yet inside psychology – focuses on precise predictions. However, both alternatives often provide little insight into the data. We propose a combination of formal modeling and Bayesian statistical inference to ground explanations in data analysis. We support this approach by reference to philosophy of science and discussions of the current methods crisis in several empirical sciences and illustrate it with an example from visual attention research.

Die Ethik der Künstlichen Intelligenz - Alpsancar, Suzana (BTU News - September 2018)

Technikfolgenabschätzung als Zeitdiagnose - Alpsancar, Suzana (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Ropohl plädiert in seiner Technikphilosophie für eine bewusste Gestaltung des technischen Wandels, in dem auch die Ingenieur*innen in die Pflicht genommen werden. In meiner Rekonstruktion zeige ich, dass Ropohls normative Grundorientierung in einer Zeitdiagnose fußt, die er allerdings nicht expliziert. Aus seinem Beispiel ziehe ich die These, dass jeder Theorie der Technikfolgenabschätzung (TA) notwendig eine historisch-normative Signatur eingeschrieben ist. Um eine kritische Auseinandersetzung über das Selbstverständnis und den Zweck von TA zu führen, gilt es, anders als Ropohl, auch die inhärenten Zeitdiagnosen sichtbar zu machen und zu diskutieren.
Keywords: General Medicine

Modellbasierter Entwurf intelligenter mechatronischer Systeme mithilfe semantischer Technologien - Oestersötebier, Felix

On Efficiently Solvable Cases of Quantum k-SAT - Aldi, Marco; de Beaudrap, Niel; Gharibian, Sevag; Saeedi, Seyran (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The constraint satisfaction problems k-SAT and Quantum k-SAT (k-QSAT) are canonical NP-complete and QMA_1-complete problems (for k >= 3), respectively, where QMA_1 is a quantum generalization of NP with one-sided error. Whereas k-SAT has been well-studied for special tractable cases, as well as from a parameterized complexity perspective, much less is known in similar settings for k-QSAT. Here, we study the open problem of computing satisfying assignments to k-QSAT instances which have a "matching" or "dimer covering"; this is an NP problem whose decision variant is trivial, but whose search complexity remains open. Our results fall into three directions, all of which relate to the "matching" setting: (1) We give a polynomial-time classical algorithm for k-QSAT when all qubits occur in at most two clauses. (2) We give a parameterized algorithm for k-QSAT instances from a certain non-trivial class, which allows us to obtain exponential speedups over brute force methods in some cases by reducing the problem to solving for a single root of a single univariate polynomial. (3) We conduct a structural graph theoretic study of 3-QSAT interaction graphs which have a "matching". We remark that the results of (2), in particular, introduce a number of new tools to the study of Quantum SAT, including graph theoretic concepts such as transfer filtrations and blow-ups from algebraic geometry; we hope these prove useful elsewhere.
Keywords: search complexity; local Hamiltonian; Quantum SAT; algebraic geometry

Quantum Generalizations of the Polynomial Hierarchy with Applications to QMA(2) - Gharibian, Sevag; Santha, Miklos; Sikora, Jamie; Sundaram, Aarthi; Yirka, Justin (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The polynomial-time hierarchy (PH) has proven to be a powerful tool for providing separations in computational complexity theory (modulo standard conjectures such as PH does not collapse). Here, we study whether two quantum generalizations of PH can similarly prove separations in the quantum setting. The first generalization, QCPH, uses classical proofs, and the second, QPH, uses quantum proofs. For the former, we show quantum variants of the Karp-Lipton theorem and Toda's theorem. For the latter, we place its third level, Q Sigma_3, into NEXP using the Ellipsoid Method for efficiently solving semidefinite programs. These results yield two implications for QMA(2), the variant of Quantum Merlin-Arthur (QMA) with two unentangled proofs, a complexity class whose characterization has proven difficult. First, if QCPH=QPH (i.e., alternating quantifiers are sufficiently powerful so as to make classical and quantum proofs "equivalent"), then QMA(2) is in the Counting Hierarchy (specifically, in P^{PP^{PP}}). Second, unless QMA(2)= Q Sigma_3 (i.e., alternating quantifiers do not help in the presence of "unentanglement"), QMA(2) is strictly contained in NEXP.
Keywords: Complexity Theory; Quantum Computing; Polynomial Hierarchy; Semidefinite Programming; QMA(2); Quantum Complexity

The Complexity of Simulating Local Measurements on Quantum Systems - Gharibian, Sevag; Yirka, Justin (12th Conference on the Theory of Quantum Computation, Communication and Cryptography (TQC 2017))
An important task in quantum physics is the estimation of local quantities for ground states of local Hamiltonians. Recently, Ambainis defined the complexity class P^QMA[log], and motivated its study by showing that the physical task of estimating the expectation value of a local observable against the ground state of a local Hamiltonian is P^QMA[log]-complete. In this paper, we continue the study of P^QMA[log], obtaining the following results. The P^QMA[log]-completeness result of Ambainis requires O(log n)-local observ- ables and Hamiltonians. We show that simulating even a single qubit measurement on ground states of 5-local Hamiltonians is P^QMA[log]-complete, resolving an open question of Ambainis. We formalize the complexity theoretic study of estimating two-point correlation functions against ground states, and show that this task is similarly P^QMA[log]-complete. P^QMA[log] is thought of as "slightly harder" than QMA. We justify this formally by exploiting the hierarchical voting technique of Beigel, Hemachandra, and Wechsung to show P^QMA[log] \subseteq PP. This improves the containment QMA \subseteq PP from Kitaev and Watrous. A central theme of this work is the subtlety involved in the study of oracle classes in which the oracle solves a promise problem. In this vein, we identify a flaw in Ambainis' prior work regarding a P^UQMA[log]-hardness proof for estimating spectral gaps of local Hamiltonians. By introducing a "query validation" technique, we build on his prior work to obtain P^UQMA[log]-hardness for estimating spectral gaps under polynomial-time Turing reductions.
Keywords: Complexity theory; Quantum Merlin Arthur (QMA); local Hamiltonian; local measurement; spectral gap

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (ACM Transactions on Computation Theory (TOCT))
Keywords: Local Hamiltonian; ground state connectivity; quantum Hamiltonian complexity; reconfiguration problem

The Online Advertising Tax. A Digital Policy Innovation. CAMRI Policy Briefs No. 1. (Short version) - Fuchs, Christian

The Online Advertising Tax as the Foundation of a Public Service Internet - Fuchs, Christian

Nationalism 2.0. The Making of Brexit on Social Media - Fuchs, Christian

Karl Marx @ 200. Debating Capitalism & Perspectives for the Future of Radical Theory - Fuchs, Christian; Monticelli, Lara (tripleC: Communication, Capitalism & Critique)